Hubungan Pelaksanaan Discharge Planning dengan Kesiapan Pulang Keluarga Pasien Anak dengan Tuberkulosis Paru di RSUD Kabupaten Karawang - Sep Carliyan; Ana Rizana (Universitas Malahayati, 2026)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Pulmonary tuberculosis is characterized by coughing with phlegm for approximately 2 weeks. Coughing with phlegm mixed with blood, coughing up blood, shortness of breath, weakness, decreased appetite, weight loss, malaise, night sweats, fever accompanied by chills for more than a month. Some patients with pulmonary tuberculosis must undergo hospitalization. During hospitalization, patients with pulmonary tuberculosis require various professional actions. Many aspects need to be communicated, including knowledge, information, care, improving health status and treatment compliance and prevention of transmission. To determine the relationship between the implementation of discharge planning and the readiness to go home of families of pediatric patients with pulmonary tuberculosis at the Karawang District Hospital. The research sample was taken using the accidental sampling technique. This study used a quantitative descriptive analytical research design with a cross-sectional design. The data collection tool used a questionnaire sheet. The study showed that respondents who assessed the implementation of Discharge Planning in the good category had a readiness to go home value in the good category, which was 82.6%. From the results of the statistical test (Chi Square), a p value of 0.000 alpha (0.05) was obtained, so Ho was rejected/Ha was accepted, meaning that there was a significant statistical relationship between the implementation of discharge planning and the readiness to go home of the families of pediatric patients with pulmonary tuberculosis at the Karawang Regency Hospital in 2024. From this study, there is a significant relationship between the implementation of discharge planning and the readiness to go home of the families of pediatric patients with pulmonary tuberculosis at the Karawang Regency Hospital in 2024. Keywords: Tuberculosis Concept, Implementation of Discharge Planning, and Concept Readiness to Go Home, Family Concept. ABSTRAK Tuberkulosis (TB) adalah penyakit infeksi yang disebabkan oleh bakteri Mycobacterium tuberkulosis. Tuberkulosis paru ditandai dengan batuk disertai dahak selama kurang lebih 2 minggu. Batuk disertai dengan dahak yang bercampur darah, batuk berdarah, sesak nafas, badan lemas, nafsu makan menurun, berat badan menurun, malaise, berkeringat pada malam hari, demam disertai meriang lebih dari satu bulan. Beberapa penderita tuberkulosis paru harus menjalani perawatan di rumah sakit. Selama perawatan di rumah sakit pasien dengan tuberkulosis paru membutuhkan berbagai macam tindakan yang bersifat professional. Banyak aspek yang perlu dikomunikasikan diantaranya pengetahuan, informasi, perawatan, meningkatkan status kesehatan dan kepatuhan pengobatan maupun pencegahan penularan. Mengetahui Hubungan pelaksanaan discharge planning dengan kesiapan pulang keluarga pasien anak dengan tuberkulosis paru di RSUD Kabupaten Karawang. Pengambilan sampel penelitian menggunakan Teknik accidental sampling. Penelitian ini menggunakan desain penelitian kuantitatif deskriptif analitik dengan rancangan cross sectional. Alat pengumpulan data menggunakan lembar kuesioner. Penelitian menunjukkan bahwa responden yang menilai pelaksanaan Discharge Planning dalam kategori baik memiliki nilai kesiapan untuk pulang dalam kategori baik pula yaitu sebesar 82,6%. Dari hasil uji statistik (Chi Square) diperoleh nilai p value 0,000 alpha (0,05) maka Ho ditolak/Ha diterima, artinya terdapat hubungan statistik yang bermakna antara pelaksanaan discharge planning dengan kesiapan pulang keluarga pasien anak dengan tuberkulosis paru di RSUD Kabupaten Karawang tahun 2024. Dari penelitian ini adalah ada hubungan yang bermakna antara pelaksanaan discharge planning dengan kesiapan pulang keluarga pasien anak dengan tuberkulosis paru di RSUD Kabupaten Karawang tahun 2024. Kata Kunci: Konsep Tuberkulosis, Pelaksanaan Discharge Planning, dan konsep Kesiapan Pulang, Konsep Keluarga.